1998
DOI: 10.1144/gsl.sp.1998.141.01.02
|View full text |Cite
|
Sign up to set email alerts
|

Compaction — the great unknown in basin modelling

Abstract: Decompaction routines are used in basin modelling packages to calculate sediment thickness and material properties such as thermal conductivity. However, compaction in nature is dependent on initial porosity, composition, and effective stress, and a considerable range of porosity-depth trends exists. Simple thermal modelling demonstrates that significant uncertainties (up to VRE ± 0.5) arise in predicted maturities due to this variation. Furthermore, the validity of using porosity loss as a measure of compacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 38 publications
3
50
0
Order By: Relevance
“…Increasing the effective porosity from 1.4 to 3.1% can account for the observed decrease in resistivity. These porosity values are reasonable and in agreement with studies of near surface materials (Giles et al 1998). Alternatively, the change in resistivity could be explained by maintaining a constant porosity, but increasing the saturation.…”
Section: Evidence For Time Variations In Resistivitysupporting
confidence: 89%
See 1 more Smart Citation
“…Increasing the effective porosity from 1.4 to 3.1% can account for the observed decrease in resistivity. These porosity values are reasonable and in agreement with studies of near surface materials (Giles et al 1998). Alternatively, the change in resistivity could be explained by maintaining a constant porosity, but increasing the saturation.…”
Section: Evidence For Time Variations In Resistivitysupporting
confidence: 89%
“…Measurements on the core recovered from the A-hole by Tanaka et al (2006) reported porosity values of 8% and 30% at 1000 and 1300 m depth, respectively. Porosity typically decreases exponentially with depth (Rubey and Hubbert 1959;Giles et al 1998). However, in this case, the increase in porosity with depth is likely associated with the damage zone associated with the Chelungpu Fault zone.…”
Section: Inversion Of the Amt Datamentioning
confidence: 99%
“…Giles et al (1998) introduced new parameter τ , and coupled the velocity to effective stress via empirical constants as:…”
Section: Conventional Bowers and Tau Methodsmentioning
confidence: 99%
“…proposed a power-law relationship between compressional velocity and effective stress by calculating the overburden stress and predict the pore pressure at offset well locations. Similarly, Giles et al (1998) introduced a compound mudline and matrix-transittime variable (Tau) as a first-order effective stress versus velocity power-law relationship. Later, Boitnott et al (2009) improved Bowers method by considering a normal compaction trend that is asymptotic to matrix velocities and can provide a better representation of the physical properties of the rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Historically basin models have only been able to simulate mechanical compaction, for example by using an elastoplastic effective-stress law (Giles et al, 1998). Normally the modeler defines this law using a porosity-depth curve such as Curve B.…”
Section: Overpressure and Leakage Modeling In The Western Halten Bankmentioning
confidence: 99%